The Difference of Gastric pH in Dyspepsia Patients With or Without Type 2 Diabetes Mellitus - Ilum Anam; Ari Fahrial Syam; Dante Saksono Harbuwono (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Dyspepsia syndrome often experienced by patients with diabetes mellitus (DM). Gastric acid is one of the aggressive factors of syndrome dyspepsia and peptic ulcers. This study aims to find the difference of gastric pH in dyspepsia patients with DM and without DM, and also to determine whether there is any correlation between gastric pH with proteinuria and hemoglobin A1c (HbA1c).Method: Two groups of patients consisted of 30 patients with DM and 30 patients without DM. Basal gastric pH of each group counted. Basal gastric pH was measured by inserting electrode catheter into the stomach for 30 minutes and then recorded on PH Metri brand Digitrapper pH-Z. Complication of DM was measured by microalbuminuria, while blood sugar control was measured by HbA1c. Chi-square test was done to look for difference of gastric pH between the diabetic patients group and non-diabetic patients group, by first determining the point of intersection with receiver operating characteristic (ROC) analysis. Correlation test between basal gastric pH with microalbuminuria and HbA1c were done.Results: Basal gastric pH in dyspepsia patients with DM vs. dyspepsia patients without DM was 2.30 ± 0.83 vs. 2.19 ± 0.52. With the Chi-square test, there is a significant difference between the diabetic patients group and non-diabetic patients group. With the correlation test between gastric pH and microalbuminuria was found r = 0.47 and p 0.05, whereas the correlation test between gastric pH and HbA1c was found r = 0.59 and p 0.05.Conclusion: There is a significant difference between basal gastric pH in diabetic dyspepsia patients and non-diabetic dyspepsia patients. There is a correlation between basal gastric pH and microalbuminuria, whereas there is no correlation between basal gastric pH and HbA1c.